Elections and fiscal policy at the municipal level in Brazil - Klein, Fabio Alvim (2012)
This thesis adds to the political business cycles (PBC) literature by studying the relationships between elections, term limits, political parties and fiscal policies in 3,393 Brazilian municipalities between 2001 and 2008. The results show that first term mayors increase total revenues and keep reasonable levels of spending during elections, thus preserving or either increasing budget balances. They also change their budget composition from current expenditures (e.g. personnel) towards capital related ones (e.g. investments) as elections approach. In fact, only first term mayors seem to benefit from opportunistic increases in fiscal variables, especially in current and personnel expenditures. Yet, first term mayors are not necessarily less fiscally responsible than second term mayors along their term in office (non-electoral years) or during elections. In this sense, elections with first term and second term mayors seem to promote a competitive feature which appears to enhance electoral and fiscal accountability. This thesis also points at a significant association between opportunistic and partisan fiscal cycles at the local level in Brazil. During elections, rightwing parties increase the budget balance, while left-wing parties increase capital related expenditures and reduce current and personnel expenditures, but in this last case not as much as other parties. By doing so, these parties partially meet voters’ fiscal preferences. During the term (non-electoral years), however, right-wing parties present a slightly looser budget balance, while left-wing parties invest less than other parties, and these policies are not favoured by voters. Overall, this study shows that voters in Brazil recognize a sustainable fiscal management, enjoying both higher government revenues and spending, especially rewarding higher capital expenditures and investments throughout the incumbent’s term and increases in current and personnel expenditures in the electoral year. In any case, voters’ fiscal preferences are mostly independent of ideological preferences.